1986
DOI: 10.1002/jsfa.2740370509
|View full text |Cite
|
Sign up to set email alerts
|

Influence of repeated frying on the digestive utilisation of various fats

Abstract: Three types of fat, olive oil, soya bean oil and a solid cooking fat were used to fry potatoes, lean beef or sardines. The heating cycle was carried out once and repeated ten times and the true digestibility (TD) and energy digestibility (ED) determined by feeding trials on rats. The results showed very little change in either measurement compared with the fresh, unheated fats. Discarded olive oil from an industrial fryer was also examined and found to be only slightly lower in TD and E D than after ten cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
4
1
0
Order By: Relevance
“…The significant decrease in the true digestibility coefficient of whole palm olein seen in this study concurs with previous results of other authors (Alexander, 1966;Nolen, 1973). However, research conducted by Lanteaume et al (1966), Le Floch et al (1968), andVarela et al (1986) did not find important effects on the fat digestibility of different oils used for frying. Some years ago, Crampton et al (1953) reported that the principal reason for the lower nutritive value of diets that included linseed oil heated to 275 °C was the presence of one or more dimer fatty acid radicals in this polymerized fat.…”
Section: Discussionsupporting
confidence: 92%
“…The significant decrease in the true digestibility coefficient of whole palm olein seen in this study concurs with previous results of other authors (Alexander, 1966;Nolen, 1973). However, research conducted by Lanteaume et al (1966), Le Floch et al (1968), andVarela et al (1986) did not find important effects on the fat digestibility of different oils used for frying. Some years ago, Crampton et al (1953) reported that the principal reason for the lower nutritive value of diets that included linseed oil heated to 275 °C was the presence of one or more dimer fatty acid radicals in this polymerized fat.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, FT, NFT, FC, and NFC rats displayed oil digestibility values of 51.5%, 62.6%, 67.7%, and 72.0%, respectively, suggesting that true digestibility of sunflower oil used in frying was lower than that of unused sunflower oil, coinciding with previous data from other authors (8,9). However, research conducted by Lanteaume et al (35), Le Floch et al (36), and Varela et al (37) did not conclude that digestibility of different oils used for frying varied to any great degree in relation to unused oils. Some years ago, Crampton et al (38) reported that the low nutritive value of diets that included linseed oil heated to 275 °C was principally due to the presence of one or more fatty acid radicals in this polymerized fat.…”
Section: Discussionsupporting
confidence: 89%
“…The non significant differences between true digestibility coefficient at the 40th and 90th frying are in accordance with the results obtained by other authors, who found a similar di-gestibility coefficient in various fats and oils used in frying [40,41].…”
Section: Animals and Maintenancesupporting
confidence: 92%